2015
DOI: 10.4238/2015.september.21.14
|View full text |Cite
|
Sign up to set email alerts
|

Gene and protein expression in the oxaliplatin-resistant HT29/L-OHP human colon cancer cell line

Abstract: ABSTRACT. Oxaliplatin (L-OHP) is one of the most commonly used anticancer drugs in adjuvant treatment of colon cancer after complete resection of the primary tumor and treatment of metastatic colorectal cancer. Cancer cells eventually become resistant to L-OHP, which diminishes its curative effect. However, the mechanism of action of L-OHP remains unknown. In this study, an L-OHP-resistant human colon cancer cell line, HT29/L-OHP, was established by gradually increasing the dose of L-OHP in culture. The expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…Similarly, increased expression of the inhibitor of apoptosis BIRC4 (XIAP) could also contribute to oxaliplatin resistance and counteract the increased expression of the cell death execution caspases 6 and 7 in the platinum-resistant ovarian cancer cell lines. These data are in line with the decrease in annexin A3 in l-OHP resistant colon cancer cells [43], as well as an activation of mutated p53 in l-OHP resistant ovarian cancer cells [44] and a change in multiple apoptosis regulating genes in resistant colon cancer cells [45].…”
Section: Discussionsupporting
confidence: 71%
“…Similarly, increased expression of the inhibitor of apoptosis BIRC4 (XIAP) could also contribute to oxaliplatin resistance and counteract the increased expression of the cell death execution caspases 6 and 7 in the platinum-resistant ovarian cancer cell lines. These data are in line with the decrease in annexin A3 in l-OHP resistant colon cancer cells [43], as well as an activation of mutated p53 in l-OHP resistant ovarian cancer cells [44] and a change in multiple apoptosis regulating genes in resistant colon cancer cells [45].…”
Section: Discussionsupporting
confidence: 71%
“…In many cases, extensive DNA damage leads to activation of cell cycle check points and results in cell cycle arrest and apoptosis (32). Previous studies have shown that ACBP promoted cell proliferation in GC cells and inhibited MGC-803 cancer cells (17) and L-OHP-resistant human colon cancer cell lines with increasing dose of L-OHP in culture (33). In this study, we found that A+L induced apoptosis in MKN-45 cells, which was revealed by the PI assay.…”
Section: Discussionsupporting
confidence: 62%
“… 38 – 40 The result showed that the L-OHP–resistant cell line acquired resistance to apoptosis by activation of PI3K/AKT signaling pathway, upregulation of Bcl-2 and downregulation of Bax. 41 The inactivated PI3K/AKT signaling pathway promoting apoptosis induced a reduction of the Bcl-2/Bax ratio, eventually triggering caspase-3 activation and inducing apoptosis. 42 Similarly, we found that knockdown of KLK11 inactivated the PI3K/AKT signaling pathway, increased the Bax expression, and decreased the Bcl-2 expression, which led to a reduction of the Bcl-2/Bax ratio.…”
Section: Discussionmentioning
confidence: 99%